ANTIBACTERIAL AND ANTIOXIDANT PROPERTIES OF OCIMUM SANCTUM EXTRACTS AGAINST STREPTOCOCCUS MUTANS AND ESCHERICHIA COLI (Journal of Medical & Health Sciences Review, 2025)
The rise of antibiotic-resistant bacteria has increased the demand for alternative antimicrobial and antioxidant agents. Ocimum sanctum (holy basil) is widely recognized for its medicinal properties, particularly its antibacterial and antioxidant potential. This study evaluates the antibacterial activity of O. sanctum extracts against Streptococcus mutans and Escherichia coli, comparing ethanol, methanol, and aqueous extractions. The study also investigates the dose-response relationship, minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and antioxidant potential of the extracts. O. sanctum extracts were prepared using ethanol, methanol, and aqueous solvents. The antibacterial activity was assessed using the disc diffusion method at different extract concentrations (10, 25, 50, 75, and 100 mg/mL). The MIC and MBC values were determined using the broth dilution method, while a time-kill assay monitored bacterial reduction over 24 hours. The antioxidant activity of the extracts was analyzed using the DPPH radical scavenging assay to evaluate their free radical neutralization ability. The ethanol extract exhibited the highest antibacterial activity, with inhibition zones of 28.6 ± 1.3 mm for S. mutans and 33.2 ± 1.4 mm for E. coli at 100 mg/mL. The MIC values for ethanol extract were 6 mg/mL for S. mutans and 4 mg/mL for E. coli, while MBC values were 12 mg/mL and 8 mg/mL, respectively. The time-kill assay demonstrated that 18 mg/mL ethanol extract reduced bacterial counts by 99.9% within 24 hours, whereas methanol and aqueous extracts required higher concentrations (30 mg/mL and 60 mg/mL). The antioxidant assay showed that ethanol extract had the highest free radical scavenging activity (82.5 ± 2.1%) compared to methanol (76.3 ± 1.8%) and aqueous extracts (64.7 ± 1.5%). The findings suggest that O. sanctum extract, particularly in ethanol form, possesses significant antibacterial and antioxidant properties. Its strong antimicrobial activity and free radical scavenging potential highlight its role as a natural therapeutic agent. Further in vivo and clinical studies are needed to validate its effectiveness in pharmaceutical and nutraceutical applications.